Predicting complications in partial nephrectomy for T1a tumours: does approach matter?. (11th August 2016) - Ramirez, Daniel; Maurice, Matthew J.; Caputo, Peter A.; Nelson, Ryan J.; Kara, Önder; Malkoç, Ercan; Kaouk, Jihad H.
Abstract : Objectives: To assess differences in complications after robot‐assisted (RAPN) and open partial nephrectomy (OPN) among experienced surgeons. Patients and Methods: We identified patients in our institutional review board‐approved, prospectively maintained database who underwent OPN or RAPN for management of unifocal, T1a renal tumours at our institution between January 2011 and August 2015. The primary outcome measure was the rate of 30‐day overall postoperative complications. Baseline patient factors, tumour characteristics and peri‐operative factors, including approach, were evaluated to assess the risk of complications. Results: Patients who underwent OPN were found to have a higher rate of overall complications (30.3% vs 18.2%; P = 0.038), with wound complications accounting for the majority of these events (11.8% vs 1.8%; P < 0.001). Multivariable logistic regression analysis showed the open approach to be an independent predictor of overall complications (odds ratio 1.58, 95% confidence interval 1.03–2.43; P = 0.035). Major limitations of the study include its retrospective design and potential lack of generalizability. Conclusions: The open surgical approach predicts a higher rate of overall complications after partial nephrectomy for unifocal, T1a renal tumours. For experienced surgeons, the morbidity associated with nephron‐sparing surgery may be incrementally improved using the robot‐assisted approach.